Disaggregating data: The only way to answer a gender question in research - Ndiwa, Nicholas N. (International Livestock Research Institute, 2016)
Gender-disaggregated data are the only way we can answer a gender question. Analysing gender-disaggregated data is challenging but interesting. One of the most interesting findings from the research relates to asset ownership: it is necessary to look at the proportion of assets owned by women or men in each household, instead of the absolute number of assets each owns. Interview with Nicholas Ndiwa (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684